Synthesis of potential fuel additives via interaction of isoprene with various classes of oxygen-containing compounds - I. Sh. Khusnutdinov; I.N. Goncharova; A.G. Safiulina; D.N. Safina (Egyptian Journal of Petroleum)
Unstable market of conventional fuel resources with the high fluctuation of oil prices is shifting interest towards obtaining fuels from renewable components. Unsaturated aliphatic hydrocarbons, produced in oil refineries and from renewable bioresources, present a potential feedstock for the production of oxygen-containing additives for motor fuels. In the present paper the interaction of the simplest representative of diene series – isoprene with various classes of oxygen-containing compounds: ethyl alcohol, acetic acid, acetaldehyde, produced from biomass as well, is analyzed. The possibility of synthesizing of various acetals and paraldehyde, proposed as potential high-quality fuel additives, via interaction of isoprene with ethyl alcohol and acetaldehyde, is shown. Within the first series of experiments, sufficiently high yields of products are obtained. Yield of potential oxygen containing additives to gasoline produced via interaction of isoprene with ethanol exceeds 15 %, via interaction of isoprene with acetaldehyde: potential diesel additives −40 %, gasoline additives −12.9 %.